Development of a novel gout treatment patient decision aid by patient and physician: A qualitative research study - Meykkumar Meyappan; Wei Siong Aaron Loh; Li Yen Tan; Sheng Feng Ian Tan; Pey Ying Ho; Yih Jia Poh; Ngiap Chuan Tan (Wiley, 2021)
Abstract Background Gout treatment is not optimized globally, often due to therapeutic inertia by physicians or poor adherence to urate‐lowering medications by patients. A patient decision aid (PDA) to facilitate shared decision making (SDM) in gout treatment may overcome these physician‐patient barriers. Objective The study explored the views of physicians and patients on a novel locally designed gout treatment PDA prototype. Design Qualitative descriptive design was used to gather data from in‐depth‐interviews (IDI) and focus group discussions (FGD). Data analysis was via thematic analysis. Emergent themes shaped a revised version of the PDA. Setting and participants Adult Asian patients with recent acute gout exacerbations and local Primary Care Physicians (PCP) in Singapore were purposefully chosen. 15 patients with gout and 11 PCPs participated across three IDIs and six FGDs, with the investigators exploring their views of a prototype gout treatment PDA. Results Patients and physicians generally concurred with the content and design of the PDA prototype. However, while patients preferred fewer treatment details, the PCPs desired more information. Patients preferred the display of statistics, while PCPs felt that numbers were not relevant to patients. The latter were hesitant to include treatment options that were unavailable in primary care. Both stakeholders indicated that they would use the PDA during a consultation. PCPs would need further training in SDM, given a lack of understanding of it. Conclusion and patient contribution Patients will be the prime users of the PDA. While their views differed partially from the physicians, both have jointly developed the novel gout treatment PDA.